Subsidized housing and school segregation: Examining the relationship between federally subsidized affordable housing and racial and economic isolation in schools - Holme, Jennifer Jellison; Frankenberg, Erica; Sanchez, Joanna; Taylor, Kendra; De La Garza, Sarah; Kennedy, Michelle (Education Policy Analysis Archives, 2020)
Each year, the federal government provides billions of dollars in support for low-income families in their acquisition of housing. In this analysis, we examine how several of these subsidized housing programs, public housing and Low Income Housing Tax Credit (LIHTC) financed housing, relate to patterns of school segregation for children. We use GIS to examine the location of subsidized housing vis-à-vis district boundaries and school attendance boundaries in four Texas counties. We then examine patterns of segregation between schools with and without subsidized housing in their attendance zones, as well as the extent of economic and racial isolation experienced by students in those schools. Our results illustrate that public housing and LIHTC housing developments are zoned to racially and economically isolated schools, and that developments are associated with especially high levels of economic and racial isolation for Black and Latinx students. We conclude by discussing implications for housing and education policy to ameliorate these patterns.